2013
DOI: 10.3109/02713683.2013.802809
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSimulation of Corneal Epithelium Microenvironment Induces a Corneal Epithelial-like Cell Phenotype from Human Adipose Tissue Mesenchymal Stem Cells

Abstract: Corneal epithelial-like cells can be induced from extraocular hAT-MSCs by subjecting them to an in vitro microenvironment containing conditioning signals derived from differentiated human corneal epithelial cells. Our results suggest that hAT-MSCs could provide a novel source of stem cells that hold the potential to restore sight lost in patients suffering from bilateral ocular surface failure due to LSCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 46 publications
3
48
0
6
Order By: Relevance
“…Several therapeutic approaches with alternative stem cells, such as mesenchymal stem cells (MSC) [1216], cultured oral mucosa epithelial cells [17, 18], embryonic stem cells (ESC) [19], or induced pluripotent stem cells (IPSC) [2022], have been established to either study their potential to differentiate into corneal epithelium phenotypes or to reconstruct a damaged corneal epithelium in experimental models. However, several key issues remain unresolved and these options require a great deal of development before they are ready for clinical application in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Several therapeutic approaches with alternative stem cells, such as mesenchymal stem cells (MSC) [1216], cultured oral mucosa epithelial cells [17, 18], embryonic stem cells (ESC) [19], or induced pluripotent stem cells (IPSC) [2022], have been established to either study their potential to differentiate into corneal epithelium phenotypes or to reconstruct a damaged corneal epithelium in experimental models. However, several key issues remain unresolved and these options require a great deal of development before they are ready for clinical application in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Inducing MSCs in the AM significantly improves the reconstruction of the corneal surface of rats with corneal alkali burn. In a recent in vitro experiment, corneal epithelia-like cells were induced from human adipose tissue-derived MSCs by subjecting them to a medium conditioned with corneal epithelial cells [53] . In addition, MSCs can differentiate into corneal epithelial progenitor cells in Rb-LSC deficiency models [54] .…”
Section: Msc Mobilization and Homingmentioning
confidence: 99%
“…Optical PK following the COMET treatment has been reported by a group to achieve good improvement in the visual outcome with a stable corneal graft (Ma et al 2009 ). Recent studies have also shown that mesenchymal stem cells derived from various sources such as bone marrow, dental pulp, adipose tissues and limbal stroma are effective in controlling infl ammation and regeneration of corneal surface (Gu et al 2009 ;Gomes et al 2010 ;Nieto-Miguel et al 2013 ;Rohaina et al 2014 ;Katikireddy et al 2014 ;Acar et al 2015 ;Syed-Picard et al 2015 ). Another group has reported the presence of stromal stem cells at the limbal niche and demonstrated the usefulness of these autologous, mesenchymal-like stem cells in the treatment of corneal stromal scars (Li et al 2012 ;Basu et al 2014 ).…”
Section: Alternate Stem Cell Sources and Treatment Modalities For Ocumentioning
confidence: 99%